The Effect of the Project-Based Learning (PBL) Model in the “Virtuous Character” Unit on the Behavior of Ninth-Grade Students in the “Akidah Akhlak” Course at MTs Darul Ihsan Anggana - Habib Zainuri; Siti Rabiatul Aliyah; Budi Yusuf (PT Publikasiku Academic Solution, 2026)
This study was motivated by the persistence of behavioral issues among Grade IX students, particularly concerning discipline and attitudes toward teachers, as well as the learning process, which tended to be monotonous due to the predominant use of the lecture method. Therefore, an innovative instructional model such as Project-Based Learning (PjBL) is required to enhance student engagement and to cultivate the practice of praiseworthy morals. This study aims to describe the implementation of the PjBL model, to examine the condition of students’ behavior, and to determine the extent of the influence of the PjBL model on students’ behavior in the Aqidah Akhlak subject at MTs Darul Ihsan Anggana. This research employed a quantitative approach with an associative research design. Data were collected through the distribution of questionnaires to the respondents. The collected data were analyzed using descriptive statistical techniques in the form of percentage index analysis, as well as inferential statistical methods, including the Classical Assumption Tests, Simple Linear Regression Analysis, Partial Test (t-test), and the Coefficient of Determination Test, with the assistance of SPSS software. The findings of this study indicate that the implementation of the PjBL model is categorized as “Very High,” with an average index score of 95.67%, and students’ behavior is also categorized as “Very High,” with an index score of 94.04%. Based on hypothesis testing, the calculated t-value of 7.057 is greater than the critical t-value of 2.013, with a significance level of 0.000 < 0.05; thus, the alternative hypothesis (Ha) is accepted. This indicates that there is a positive and statistically significant effect of the PjBL model on students’ behavior. The magnitude of this effect, as indicated by the coefficient of determination, is 50.9%, while the remaining 49.1% is influenced by other factors .